Strengthening partnership for regional sustainable development - Trần Đại Quang 1956-2018 (ISEAS Publishing, 2016)
The Singapore Lecture is designed to provide an opportunity for distinguished statesmen and leaders of thought and knowledge to reach a wider audience in Singapore. The presence of such eminent personalities allows Singaporeans, especially younger executives and decision-makers in both the public and private sectors, the benefit of exposure to leading world figures who address topics of international and regional interest. The 38th Singapore Lecture was delivered by His Excellency Tran Dai Quang, President of the Socialist Republic of Vietnam, on 30 August 2016 under the distinguished Chairmanship of Mr Teo Chee Hean, Deputy Prime Minister and Coordinating Minister for National Security, Singapore